THE PROBLEM OF EATING BEHAVIOUR IN THE FIELD OF PSYCHOLOGY - Magfirat Mirodil kizi Abdumutalibova (Web of Journals Publishing, 2025)
This article provide information about eating behaviour, eating habits and the influence of psychological factors to eating. Explains the relationship between mood and eating behaviour.
Keywords: Eating behavior, energy, rewarding behavior, binge eating disorder, bulimia nervosa.